1970
DOI: 10.3329/bjms.v8i1.3181
|View full text |Cite
|
Sign up to set email alerts
|

Medical services without medical ethics: Sailing the ship without compass

Abstract: doi: 10.3329/bjms.v8i1.3181Bangladesh Journal of Medical Science Vol.8 No. 1-2; 2009 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This situation reflects the healthcare system of that community has been failed to abide by the elementary medical ethics, regular and average processes, customs, laws, and guidelines. [68][69][70] As medical doctors are the most considerable elements in pharmaceutical transactions by choosing the specific brand of medicine for their patients. 71 Subsequently, there is an urgent need to develop scientific, ethical, and professional medicine promotional activity.…”
Section: "The Proliferation Of Medical Advertising Is a Symptom Of Thmentioning
confidence: 99%
“…This situation reflects the healthcare system of that community has been failed to abide by the elementary medical ethics, regular and average processes, customs, laws, and guidelines. [68][69][70] As medical doctors are the most considerable elements in pharmaceutical transactions by choosing the specific brand of medicine for their patients. 71 Subsequently, there is an urgent need to develop scientific, ethical, and professional medicine promotional activity.…”
Section: "The Proliferation Of Medical Advertising Is a Symptom Of Thmentioning
confidence: 99%
“…Indeed a report from an extensive literature review found that doctors are affected by their interaction with pharmaceutical industry. There is evidence to show that doctors prescribing pattern is influenced after attending industry sponsored education programs even when the program is conducted in an academic environment governed by preset ethical guidelines [10][11][12][13][14] .…”
Section: Product Marketing Promotion and Educationmentioning
confidence: 99%
“…In Bangladesh such a guideline has been in existence developed by Ethics Committee of the BMRC (Bangladesh Medical Research Council). Among the important points to highlight is that doctors should not participate in promotional activities that could in any way damage their public standing or reputation for independence of profession in the eyes of the peers, colleagues and co-workers, media, patients and their relatives and general public [10][11][12][13][14] .…”
Section: How Can Education and Promotion Co-exist In A Practical And mentioning
confidence: 99%